MICRO FINANCING SCHEMES & THEIR IMPACT ON POVERTY REDUCTION - A STUDY CONDUCTED ON MEMBERS OF SELF HELP GROUPS IN PUNJAB (INDIA) - Kaur, Tejbir; Singh, Rajdeep (International Journal of Research -GRANTHAALAYAH, 2014)
In a country like India where faster, sustainable and inclusive growth is the objective/mission of the government, there arises a need to study the impact of microfinance through SHG’s (Self Help Groups) on poverty reduction. The current study examines to what extent microfinance through SHG’s has helped the members in raising their economic status. The target population for the study was the members of SHG’s at district Fatehgarh Sahib. A sample of 100 members out of the universe was selected using convenience sampling and a survey was conducted. The reliability of data was confirmed by using cronbach’s reliability test. Descriptive statistics and cross tabulation have been used to analyze the data. The study shows a positive impact of micro financing Schemes on poverty reduction.